Hubungan antara Kepuasan Interaksi Sosial dengan Kepercayaan Diri Siswa Kelas X SMA Negeri 2 Denpasar Tahun 2026 - Agnes Marieta Janu; I Gusti Lanang Rai Arsana; Made Wery Dartiningsih (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to investigate the relationship between social interaction satisfaction and the self-confidence of Grade X students at SMA Negeri 2 Denpasar in 2026. This quantitative correlational study involved 457 Grade 10 students, with a sample of 213 selected through proportional random sampling based on Slovin's formula. Data were collected using a Likert-scale questionnaire, and the instrument's validity and reliability were tested using SPSS version 25.0 for Windows. Data analysis was conducted using descriptive statistics and product-moment correlation. The results showed a correlation coefficient (r) of 0.550 with a significance level of p < 0.05. Since the r-value exceeded the table value (0.550 > 0.134), the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected, indicating a positive and significant correlation between social interaction satisfaction and student self-confidence. Higher satisfaction with social interaction was associated with higher student self-confidence. The contribution of social interaction satisfaction to self-confidence was 30.25%, although other unexamined factors also played a role.